Effect of Thermomechanical Processing on Porosity Evolution and Mechanical Properties of L-PBF AISI 316L Stainless Steel - Patrik Petroušek; Róbert Kočiško; Andrea Kasperkevičová; Dávid Csík; Róbert Džunda (Metals, 2025)
Thermomechanical processing has a significant impact on the porosity and mechanical properties of AISI 316L stainless steel produced by laser powder bed fusion (L-PBF). This work evaluated the effect of three heat treatment conditions: as-built (HT0), annealed at 650 °C for 3 h with air cooling (HT1), and annealed at 1050 °C for 1 h followed by water quenching (HT2), combined with cold and hot rolling at different strain levels. The most pronounced improvement was observed after 20% hot rolling followed by water quenching (HR + WQ), which reduced porosity to 0.05% and yielded the most spherical pores, with a circularity factor (<semantics>fcircle</semantics>) of 0.90 and an aspect ratio (AsR) of 1.57. At elevated temperatures, the matrix becomes more pliable, which promotes pore closure and helps reduce stress concentrations. On the other hand, applying heat treatment without causing deformation resulted in the pores growing and increasing porosity in the build direction. The fractography supported these findings, showing a transition from brittle to more ductile fracture surfaces. Heat treatment combined with plastic deformation effectively reduced internal defects and improved both structural integrity and strength.